1997
DOI: 10.1136/adc.76.4.320
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and physiological responses during prone and supine sleep in early infancy

Abstract: Aims-To study the eVect of prone and supine sleep on infant behaviour, peripheral skin temperature, and cardiorespiratory parameters to aid understanding of why prone sleeping is associated with an increased risk of sudden infant death syndrome. Methods-Of 33 enrolled infants, 32 were studied at 2.5 and 28 at 5 months of age. A computer aided multichannel system was used for polysomnographic recordings. Behaviour was charted separately. Results-Prone REM (active) sleep was associated with lower frequencies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 27 publications
(18 reference statements)
2
40
1
Order By: Relevance
“…It is well established that prone sleeping is associated with an increase in temperature and peripheral vasodilation in infancy. 20,45,46 This reduction in peripheral vascular resistance stimulates a baroreflex-mediated increase in HR to maintain MAP. 19,45 This reflex response is consistent with our observations at 2 to 4 weeks and 5 to 6 months CA, where HR and temperature were increased in the prone position and MAP was maintained.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that prone sleeping is associated with an increase in temperature and peripheral vasodilation in infancy. 20,45,46 This reduction in peripheral vascular resistance stimulates a baroreflex-mediated increase in HR to maintain MAP. 19,45 This reflex response is consistent with our observations at 2 to 4 weeks and 5 to 6 months CA, where HR and temperature were increased in the prone position and MAP was maintained.…”
Section: Figurementioning
confidence: 99%
“…20,45,46 This reduction in peripheral vascular resistance stimulates a baroreflex-mediated increase in HR to maintain MAP. 19,45 This reflex response is consistent with our observations at 2 to 4 weeks and 5 to 6 months CA, where HR and temperature were increased in the prone position and MAP was maintained. In contrast, we found no increase in HR in the prone position at 2 to 3 months CA, despite the observed increase in temperature; this coincided with a tendency for MAP to be lower in the prone compared with the supine position.…”
Section: Figurementioning
confidence: 99%
“…Supine sleeping is associated with increased arousals from sleep compared with the prone sleep position. [5][6][7][8][9] The effect of swaddling on the frequency of brainstem arousals as well as full behavioral arousals is unknown. Likewise, the effect of swaddling on progression of brainstem arousals to full arousals is unknown.…”
mentioning
confidence: 99%
“…4 Studies confirm that the prone position decreases frequency of arousals. [5][6][7][8][9] Swaddled infants placed on their backs are said to "sleep better," presumably meaning that they sleep longer or with fewer arousals. Parents commonly report that infants who are back sleepers "startle themselves awake."…”
mentioning
confidence: 99%
“…7,8 Over the past 25 years, numerous studies have confirmed that infants laid prone enjoy a range of behavioral and physiological advantages. The positive consequences of prone position for sleep include: fewer awakenings and increased time in quiet sleep, 9,10 more sleep with higher arousal thresholds, [11][12][13] lower levels of activity, 14,15 enhanced respiratory control, 16 -18 and diminished heart rate variability. 11,17 Newborns laid prone cry much less than supine-lying infants 11 and have decreased energy requirements.…”
mentioning
confidence: 99%